Hydrogels for preventing post-endoscopic submucosal dissection stenosis in early esophageal cancer: a comprehensive literature review - Jialin Wu; Chuan-Guo Guo; Yan Zhao; Jiaxin Wang; Jun Liu; Peng Li (Therapeutic Advances in Gastroenterology, 2025)
Endoscopic submucosal dissection (ESD) has emerged as a cornerstone therapy for early-stage esophageal cancer due to its minimally invasive characterization and high efficacy. However, postoperative esophageal stricture remains a critical complication, particularly in cases involving circumferential mucosal defects, with reported incidence rates exceeding 80%. Conventional preventive strategies, including local or systemic steroid administration, esophageal stent placement, and repeated balloon dilation, are limited by side-effect concerns, procedural complexity, and suboptimal long-term outcomes. Recent advancements in regenerative medicine have highlighted hydrogels as innovative tissue-shielding materials with significant potential to mitigate post-ESD stenosis. These hydrophilic polymer networks exhibit unique advantages such as biocompatibility, tunable mechanical properties, and the ability to transfer therapeutic agents directly to the wound. This review synthesizes current evidence on synthetic and natural hydrogels, emphasizing their mechanisms in promoting epithelial regeneration, reducing fibrosis, and synergizing with current therapies (e.g., steroid-loaded formulations or stent placement). Key findings suggest that hydrogel-based interventions significantly lower stricture rates and minimize the need for invasive procedures, offering a promising paradigm shift in postoperative management. By bridging material science and clinical practice, this work underscores the transformative potential of hydrogels in enhancing patient quality of life following esophageal ESD.